(3GNJjGQ GdeNJGQ aj cTa GdCSQGQs
(3ChdgG (B:s
(3Chdg GdeSJYGf hYdjg GdJcdGf hSejJg hbOQJHg GdeUfa Ydi KdGKjf aUdG GdaUd GdChd ai PcQ ef GOYj GdfHhI hcTa CSQGQge s
(3BNQgG (B:s
(3bGd GdeDda hecQ GdfSGA eNdha ajgf HdG Jcdja hef CQGO Cf jQj GdYOH GdYLGH ai ecQgf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3JhHfLjf (B- (3HQdjf (B(1622) s
Keywords: (3eJaQbGJs